INTEGRASI NILAI KARAKTER DALAM PEMBELAJARAN BERBASIS KURTILAS (Kajian Peran Keteladanan Guru PAI Madrasah Aliyah di Aceh) - Zulfatmi Budiman; M. Nasir Budiman (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2020)
2013 curriculum is a curriculum that gives great attention to character education, which is characterized by fulfilling the needs of spiritual and social affection in the established Standard of Content (SI). Islamic Education Teachers are the spearhead in the implementation of character education. In carrying out their duties, in addition to having to have sufficient professional staff, PAI teachers must be role models personally and socially. Professional-paedagogic competencies, PAI Madrasah Aliyah teachers in Aceh still need training and training to improve social quality and abilities, teachers, PAI, and teachers. female students and other education personnel in Madrasas, especially in communicating with students, responsibility, dress behavior, discipline, and responsible attitude.